Supply chain disruption risk management - Ng, Bryan Zheng Yang. (2013)
In recent years, the world witnessed many unpredictable disasters. According to two independent studies, Centre for Research on the Epidemiology of Disasters (www.cred.be) claimed that the number of natural and made-made disasters has increased greatly over the last 10 years. Munich Re (www.munichre.com) reported that the average cost of these disasters has increased by a magnitude of 10 since 1960s.